Urban services growth: Influencing factors and its effect on regional growth in China - Gao, Yuan (2015)
Urban economic success depends on the growth of its services and there are various factors influencing urban services growth. However, earlier studies mostly focus on the demand and supply factors. Factors, such as the institutional environment and services spatial agglomeration, although are important in the context of urban services growth in China, are practically less emphasized. Thus, this study analyzed the contributions of demand, supply, institutional environment, and services spatial agglomeration as factors significance for urban services growth, using the hierarchical multiple regression. The Panel Unit Root Test, Panel Co-integration Model and Panel Vector Error Correction Model were used to examine the short-run and long-run effects of urban services growth on regional economic growth in China. The findings of the present study show that the demand, supply and services spatial agglomeration contributed significantly to urban services growth. However, the institutional environment had relatively smaller contributions, compared to other factors. The Error Correction Model indicated a short-run relationship, while the Panel Co-integration Model revealed the existence of a long-run relationship between urban services growth and regional economic growth in China. In conclusion, the government should implement strategies towards a more balanced urban services growth with specific priority on strategies to expand the demand and supply for urban services, improving residents’ income, to promote urbanization, and deepen division of labor as well as to increase the quality and quantity of factor inputs in urban services. Indeed, future strategies should focus more on measures to promote urban services agglomeration, while improving the urban services marketization and their openness level